Nanoporous Ge thin film production combining Ge sputtering and dopant implantation - Toinin, Jacques Perrin; Portavoce, Alain; Hoummada, Khalid; Texier, Michaël; Bertoglio, Maxime; Bernardini, Sandrine; Abbarchi, Marco; Chow, Lee (Beilstein Journal of Nanotechnology, 2015)
In this work a novel process allowing for the production of nanoporous Ge thin films is presented. This process uses the combination of two techniques: Ge sputtering on SiO2 and dopant ion implantation. The process entails four successive steps: (i) Ge sputtering on SiO2, (ii) implantation preannealing, (iii) high-dose dopant implantation, and (iv) implantation postannealing. Scanning electron microscopy and transmission electron microscopy were used to characterize the morphology of the Ge film at different process steps under different postannealing conditions. For the same postannealing conditions, the Ge film topology was shown to be similar for different implantation doses and different dopants. However, the film topology can be controlled by adjusting the postannealing conditions.
Keywords: germanium; ion implantation; porous material